Все о любви!: лучшие романтические истории для девочек / Татьяна Тронина - Тронина Татьяна (ЭКСМО, 2008)
Экземпляры: ф.14 (1.07.2008) / Инвентарный номер: 42107 / Цена: 100.00 / Авт.знак: Т 73 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4